Inhibition of glucosylceramide synthase does not reverse drug resistance in cancer cells. - Norris-Cervetto, E; Callaghan, R; Platt, F; Dwek, R; Butters, T (2004)
The multidrug-resistant cancer cell lines NCI/AdR(RES) and MES-SA/DX-5 have higher glycolipid levels and higher P-glycoprotein expression than the chemosensitive cell lines MCF7-wt and MES-SA. Inhibiting glycolipid biosynthesis by blocking glucosylceramide synthase has been proposed to reverse drug resistance in MDR cells by causing an increased accumulation of proapoptotic ceramide during treatment of cells with cytotoxic drugs. We treated both multidrug-resistant cell lines with the glucosylceramide synthase inhibitors PDMP (d-threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol), C9DGJ (N-nonyl-deoxygalactonojirimycin) or C4DGJ (N-butyl-deoxygalactonojirimycin). PDMP achieved a significant reversal of drug resistance in agreement with previous reports. However, the N-alkylated iminosugars C9DGJ and C4DGJ, which are more selective glucosylceramide synthase inhibitors than PDMP, failed to cause any reversal of drug resistance despite depleting glycolipids to the same extent as PDMP. Our results suggest that (a) inhibition of glucosylceramide synthase does not reverse multidrug resistance and (b) the chemosensitization achieved by PDMP cannot be caused by inhibition of glucosylceramide synthase alone.